The Influence of Work Spirit and Organizational Commitment on Job Satisfaction of Civil Servants at the Department of Social Affairs, Women Empowerment, Child Protection, and Family Planning of Sanggau Regency - Desi Purwanti; Irfan Mahdi (SAINTIS Publishing, 2025)
This study aims to examine the influence of work spirit and organizational commitment on job satisfaction among civil servants at the Department of Social Affairs, Women Empowerment, Child Protection, and Family Planning of Sanggau Regency. The research employed a quantitative associative approach involving 44 respondents. Data were collected through questionnaires and interviews, and analyzed using multiple linear regression analysis with the assistance of SPSS version 25. The results indicate that the regression model is significant with F(2,41) = 17.931, p 0.001, showing a strong relationship (R = 0.683) and a contribution of R² = 0.466. Partially, work spirit has a positive and significant effect on job satisfaction, and organizational commitment also has a positive and significant effect on job satisfaction. This finding suggests that the higher the employees’ enthusiasm and commitment, the greater their job satisfaction will be. The study recommends enhancing employee motivation, implementing performance-based rewards, and fostering a more participatory work culture. Future research is advised to include additional variables such as leadership style and work environment to obtain more comprehensive and in-depth results.